2019
DOI: 10.32615/ps.2019.100
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin confers drought stress tolerance in soybean (Glycine max L.) by modulating photosynthesis, osmolytes, and reactive oxygen metabolism

Abstract: In order to investigate the role of melatonin in the drought tolerance, we examined pigments, gas exchange, osmolytes, and reactive oxygen radical metabolism in soybean plants. Drought declined photosynthetic pigments and caused irreversible reduction in net photosynthesis, which was followed by stomatal limitation for 5 and 10 d and nonstomatal limitation for 15 d. Soluble sugar, soluble proteins, and proline concentrations were higher in drought-stressed seedlings compared with the control. The contents of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…Plants, subjected to different environmental stresses, are continuously producing ROS such as H2O2 (Cao et al 2019). Generally, these ROS are unstable and highly reactive molecules, presenting a challenge to plant organs.…”
Section: Discussionmentioning
confidence: 99%
“…Plants, subjected to different environmental stresses, are continuously producing ROS such as H2O2 (Cao et al 2019). Generally, these ROS are unstable and highly reactive molecules, presenting a challenge to plant organs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the negative effects of drought stress were reversed by exogenous melatonin treatment in some plants, including apple [ 40 ], grape [ 41 ], cucumber [ 42 ], tomato [ 43 ], wheat [ 21 ] and maize [ 44 ]. In our previous study, it was demonstrated that exogenous melatonin treatment could improve the tolerance of drought-treated soybean [ 24 ]. However, the specific mechanisms by which melatonin alleviates drought stress is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that exogenous melatonin treatment could improve the tolerance of drought-treated soybean, which was possibly due to the enhanced content of osmolytes and higher antioxidant enzyme activities that reduced dehydration and lipid peroxidation [ 24 ]. However, there has been scarce reports on detailed mechanisms of melatonin for inducing drought resistance in soybean.…”
Section: Introductionmentioning
confidence: 99%
“…Among plant growth substances, melatonin (N-acetyl-5-methoxytryptamine) is an amazing and powerful naturally occurring antioxidant that effectively cope with the drastic effects of water deficit in plants [18,23]. Thus, melatonin is strongly recommended to mitigate drought stress in several plant species including model plants [24,25], field crops [26,27], fruit crops [28,29], vegetable crops [30,31] as well as ornamental and medicinal plants [32,33] (Table 1). Melatonin treatment ranged from a very low concentration (50 nM) in grape [34] to high dosage (1 mM) in maize [35] (Table 1).…”
Section: An Overviewmentioning
confidence: 99%
“…(ii) By increasing drought severity, melatonin, which is biosynthesized in mitochondria and chloroplasts [76,77], exhibits more defence strategies. It promotes the physiological aspects including antioxidant system [28,59] to alleviate the oxidative damage, leading to less accumulation of H2O2, O −2 and NO [26,53], less electrolyte leakage [42], lower lipid peroxidation (MDA reduction) [28,65], lower relative conductivity [57], toxic substances content easing [60] cellular redox disruption limitation [53], better nitro-oxidative homeostasis [53], and enhanced ascorbate (AsA)-glutathione(GSH) cycle capacity (higher GSH and AsA contents) [55]. Such beneficial effects are carried out by regulating the enzymatic activities such as ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD), as well as non-enzymatic antioxidants and osmoprotectants (proline and others) [45,64], and also secondary metabolites such as flavonoids, phenolics and phenylalanine ammonialyase [49].…”
Section: Anatomical Changes and Physiological Mechanismsmentioning
confidence: 99%